Los entornos virtuales de aprendizaje y su influencia en el proceso de enseñanza en los estudiantes de básica superior de la Unidad Educativa Santa Rosa de Cerritos, Bolívar 2021 - Tierra Reinoso, Ángela Alexandra (2022)
This research work has the implementation of Virtual Learning Environments (EVA) to strengthen the Teaching Process in upper elementary students of the Santa Rosa de Cerritos Educational Unit in the province of Bolívar. The type of research has a quantitative approach, the research design is non-experimental and its scope: descriptive, explanatory. The population consisted of 65 teachers from the aforementioned Educational Unit. The data collection technique was the survey and the interview, and the previously validated questionnaire was used as an instrument. The results showed that the Virtual Learning Environments and the Teaching Process have a significant value of 0.000 <0.05; This determines that the Virtual Learning Environments are significantly related to the Teaching Process. It is concluded that the implementation of Virtual Learning Environments, through the technological tools that are provided through ICT Information and Communication Technologies, have evidenced a significant improvement in the teaching process and has facilitated teachers the development of their skills. educational activities in virtuality, improving student learning.